Color concept - Hubbard, Tom; Quiller, Stephen; Crystal Productions; Crystal Video (Glenview, IL: Crystal Video, 1991)
Quiller introduces the color wheel and then demonstrates painting with five different color schemes: monochromatic, complementary, analogous, split complementary and triad. Also covers hue, value, and intensity
Camera, John Adkins ; music, Richard McCurdy ; editor, David Emrich
Artist/instructor, Stephen Quiller
Keywords: Color -- Study and teaching; Color in art; Painting -- Technique